"Texte des Versuchens": un'analisi della raccolta di collages Und. Überhaupt. Stop. di Marlene Streeruwitz - Linford, Emma (Biblioteca di Studi di Filologia Moderna, 2021)
This book is the first published analysis and interpretation of the collection of literary collages Und. Überhaupt. Stop. Collagen. 1996-2000. by Austrian writer Marlene Streeruwitz. It presents the author and body of her narrative work, analyses her programmatic poetics and investigates the collage as a technique, aesthetic principle and mode of thought, before moving on to the examination of the primary text. It thus addresses a noticeable gap in the reception of Streeruwitz' work (as this collection has been virtually ignored, also internationally) and provides methodological and aesthetic insights relevant to the analysis of other literary collages, while also providing a comprehensive resource for the study of Streeruwitz and her oeuvre.